Impact of Social Media Influencers on Shaping Brand Loyalty and Consumer Trust - Surjono, Welly (LPPM Universitas Sangga Buana, 2025)
This study aims to examine the function of social media influencers in creating brand loyalty and to examine the factors that influence consumer trust in brands through influencers. This study is necessary because social media has become a major means of interaction between brands and consumers. Through social media, businesses can build trust and confidence with consumers in a personalized and accurate way that is not possible with traditional business methods. In addition, the trust established through social relations plays an important role in increasing brand loyalty, which strengthens the long-term relationship between brands and consumers. strength. Given the high level of competition in the digital world, understanding how social media influencers can influence consumers to shape consumer perceptions and decisions is crucial to ensure a successful marketing process in the digital age. This investigation employs a quantitative methodology utilizing a Structural Equation Modeling framework. There is a strong and significant correlation between social media influencers and brand loyalty and a strong correlation between brand loyalty and customer trust, but in contrast, a weak relationship is seen between social media influencers and customer trust.